Chemical constituents from the bark of bauhinia purpurea and their NO inhibitory activities. Issue 17 (1st September 2020) - Ni, Lin; Huang, Wei; Shi, Yan; Wang, Heshan; Qiu, Yatie; Xu, Huiyou
Abstract: Phytochemical studies led to the isolation of a new phenylpropanoid glucoside, named purpuroside (1 ), along with eight known compounds (2–9 ) from the bark of Bauhinia purpurea . The structure of the new compound was elucidated on the basis of its spectroscopic data. The absolute configuration of compound 2 was verified by X-ray diffraction analysis. Compounds 1, 2, 7, 8, and 9 inhibited NO production in mouse peritoneal macrophages with IC50 values from 35.5 to 63.0  μ M. Abstract :